BIM-Based Energy Optimization – Case study of High-Rise Building in Pakistan - Hasan, Irbaz; Safdar Gardez, Syed Shujaa; Hussain, Usman (Journal of Sustainability Perspectives, 2021)
The current work analyses the energy performance of a building at the early design and planning stage for sustainability. A multistory facility has been simulated in a virtual (3D) environment using the Building Information Modelling process. Energy analysis was performed using Autodesk Insight360 in terms of kWh/m2 /yr. Sixteen (16) story building, has been assessed at its proposed location, at 8° clockwise w.r.t true North. The study observed an annual consumption of 267 kWh/m2 /yr which was further optimized by adopting different construction innovations. It has been highlighted that using virtual technology at the design stage of buildings can help to achieve an average annual energy saving of more than 50% thus supporting the goal for a sustainable future by accessing energy requirements at the early stage of design inception.